(3cJGH GdJRcjIs - (3GdMfaj GdNQGSGfj, CHh eMeO, GdnqUrOQ GdnqTpgjO, HQgGf GdCFeI, YeQ Hf YHO GdYRjR Hf YeQ Hf eGRI, (B536 (3g`s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe (B: (3MSGe GdOjf hHYO aEfj deG HcJGH TQM GdeNJUQ GdcGaj GdaJeS GdabgGA efj Cf CcJH TQM GdcJH GdJj de jPcQgG GdMGce GdTgjO bGd QVj Gddg Yfg JMJGL deYQaI cJGH GdJRcjI Edi eYQaI UhQI GdeRcj hUhQI GdJRcjIs
(3BNQgG (B:s
(3bGd GdTgGOI LGFRI dGfg dG VeGf YdjgeG hdh TgOG Ydjg HGdhOjYI HYO EfcGQg hbGd VefGgG dc HYO GfcGQg aTgGOJgeG HGWdIs
(3efbhdI ef fSNI Gdabjg TjN GdESdGe LeGd GdOjf GdMUjQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 51s
(3eYLe GdeDdajf (B2 / 562s
(3cTa GdXfhf (B2 / 1404s
(3GdLhGgQ GdeVjI (B1 / 391s
Keywords: (3Gdabg GdMfHdjs